2019
DOI: 10.3390/s19122698
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sensitivity in Raman Imaging for Thin Layered and Powdered Food Analysis Utilizing a Reflection Mirror

Abstract: Raman imaging has been proven to be a powerful analytical technique for the characterization and visualization of chemical components in a range of products, particularly in the food and pharmaceutical industries. The conventional backscattering Raman imaging technique for the spatial analysis of a deep layer suffers from the presence of intense fluorescent and Raman signals originating from the surface layer which mask the weaker subsurface signals. Here, we demonstrated the application of a new reflection am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…The intensity of the Raman modes increases with increasing calcination temperature, and this is attributed to (i) enhanced crystallinity and (ii) the resonance with laser excitation matching with the electronic absorption bands in the BiFeO 3 nanoparticles. 40,41 The observed vibrational modes are also in agreement with the reported literature. 39,42,43 Table S4 (ESI †) lists all the fitted Raman modes for the 350, 400, 500, and 600 1C annealed BiFeO 3 nanoparticle samples.…”
Section: Optical Propertiessupporting
confidence: 91%
“…The intensity of the Raman modes increases with increasing calcination temperature, and this is attributed to (i) enhanced crystallinity and (ii) the resonance with laser excitation matching with the electronic absorption bands in the BiFeO 3 nanoparticles. 40,41 The observed vibrational modes are also in agreement with the reported literature. 39,42,43 Table S4 (ESI †) lists all the fitted Raman modes for the 350, 400, 500, and 600 1C annealed BiFeO 3 nanoparticle samples.…”
Section: Optical Propertiessupporting
confidence: 91%
“…Other related work includes the demonstration of enhancements in Raman spectra for chemical samples placed on a reective substrate 21 and in Ref. 22 it was shown that a re ective silver-coated substrate o ered an enhancement of the signal from uorescently labelled dog-kidney cells with an enhancement of 3-4, which is similar to the level of enhancement of intensity determined in this paper with respect to the Raman spectrum.…”
Section: Introductionsupporting
confidence: 76%
“…Peter J. Larkin et al [15] proposed increasing the path of action between the laser and the sample by drilling a conical/cylindrical hole in the tablet, thereby provided 3-5 times enhancement of Raman signal and 2 times increase of the accuracy. Lohumi S et al [16] proposed a mirror was used to improve the detection sensitivity of Raman imaging spectroscopy, which increased the Raman signal intensity of powder samples by 2 times. Besides, it verified the feasibility of the technique used for food adulteration in the paper.…”
Section: Introductionmentioning
confidence: 99%